(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The Jizzakh region, along with many other regions of Uzbekistan, has been home to many scholars and historical sites. These monuments provide us with very important information from the distant past. In the meantime, our priority is to draw the public’s attention to these places and to pass them on to future generations as much as possible.